Circ-DONSON Knockdown Inhibits Cell Proliferation and Radioresistance of Breast Cancer Cells via Regulating SOX4. (22nd November 2021) - Zhu, Xiufang; Li, Lei
Abstract : Background . Circular RNAs have been validated as critical regulators in the development of breast cancer (BC). Circ-DONSON is involved in the progression of glioma and gastric cancer. However, the biological role of circ-DONSON in BC remains unclear, and the aim of this study was to explore the biological role of circ-DONSON in BC. Methods . Human tissue samples and BC cell lines were collected in this study. siRNAs against circ-DONSON were transfected into BC cell lines for silencing of circ-DONSON. Quantitative real-time PCR was used to test the circ-DONSON expression. Cell counting kit-8 (CCK-8), 5-bromo-2′ deoxyuridine enzyme-linked immunosorbent assay (BrdU-ELISA), colony formation, and caspase-3 activity assays were used to assess cell proliferation, cell survival, and cell viability. Western blotting analysis was used to detect the protein expression levels. Results . Our findings showed that circ-DONSON showed high expression in BC tissues and cell lines. CCK-8 and BrdU-ELISA assays showed that circ-DONSON knockdown inhibited BC cell proliferation. Moreover, cell survival, cell viability, and caspase-3 activity assays showed that circ-DONSON knockdown reduced the radioresistance of BC cells. Mechanistically, circ-DONSON regulated BC cell proliferation and radioresistance via SRY-box transcription factor 4 (SOX4). SOX4 overexpression significantly rescued the effect of circ-DONSON knockdown on BC cell proliferation and radioresistance. Moreover, circ-DONSON activated the Wnt/ β -catenin pathway in BC cells via SOX4. Conclusion . Our study concluded that circ-DONSON knockdown hindered cell proliferation and radioresistance through the SOX4/Wnt/ β -catenin pathway in BC.